Taṭbīq Namūzaj at-Taʿlīm bi al-Takhmīn li Istīʿāb al-Mufradāt al-Lugah al-ʿArabiyyah laday Talamīż Rauḍah al-Aṭfāl “Nūrul Husnayain” bi Bukittinggi - Indah Sari (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This research is about applying the guessing teaching model to comprehend the vocabulary of the Kindergarten pupils